TRANSFORMASI PENGGUNAAN UNDANGAN KONVENSIONAL KE DIGITAL DI DUSUN IV DESA TANJUNG GUSTA KECAMATAN SUNGGAL - Dedi Ignatio Naibaho; Bakhrul Khair Amal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the transformation process from conventional to digital invitations and the public perception of this change. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The informants in this study consist of the residents of Tanjung Gusta Village, invitation printing business owners, and teachers in the village. The research was conducted in Tanjung Gusta Village, Sunggal District, Deli Serdang Regency. The findings indicate that the transformation from conventional to digital invitations is influenced by several factors, including the Covid-19 pandemic, lower costs and more varied designs of digital invitations, the increasing use of smartphones and communication services, and innovations in technology utilization. Furthermore, public perceptions of this transformation vary. Digital invitations are perceived as more economical, practical, and easier to distribute, yet they also present challenges such as fraud risks, difficulties for traditional printing businesses, and reliance on internet access. Meanwhile, conventional invitations are considered more ethical and capable of strengthening social bonds but are seen as less practical due to longer production times and higher costs compared to digital invitations. The data were analyzed qualitatively based on facts obtained through observation, interviews, and documentation. Thus, this transformation requires society to adapt to technological advancements in social and cultural aspects.